A change for the better? Innovation, workplace change and employers' liability - Guthrie, Robert; Bunn, Anna (School of Business Law, Curtin Business School, Curtin University of Technology, 2008)
Innovation is part of the Rudd Federal Labor Government’s broad productivity agenda. There is an explicit focus on innovation at the Council of Australian Governments meetings. In addition, an innovation review is being conducted throughout 2008 to rationalise innovation programs around Australia. While the innovation agendas of Government, business and industry are focused on increased productivity, attracting investment and creativity, this push towards innovation often ignores change management issues which impact on worker health and may add to the hidden costs of change. Innovation has implications for employers when new technologies expose them to a range of legal obligations and liabilities. This paper broadly canvasses some of the issues relating to employers’ liabilities and innovation.